Dampak Brand Awareness Terhadap Keputusan Pembelian Produk Big Bananas Di Kota Makassar (representamen, 2023)
The impact of brand awareness on purchasing decisions Big Bananas in Makassar. This paper intends to examine how consumer choices for Big Bananas products in Makassar City are influenced by brand awareness.. Business actors are currently required to continue to innovate on products to be widely known. Marketing through social media to increase brand awareness of potential consumers so that it will cause a trigger to make a purchase. The participants in this study were those who follow an Instagram account @Big.bananass, with a sample of 346 respondents. Using questionnaire method with simple regression analysis Test, t test, R2 coefficient test using SPSS 26. This research shows brand awareness through Instagram has a significant effect on purchasing decisions. Keywords: Brand Awareness, Purchasing Decisions, Instagram, Big Bananas